The Italian 2017 Outbreak Chikungunya Virus Belongs to an Emerging Aedes albopictus–Adapted Virus Cluster Introduced From the Indian Subcontinent - Lindh, Erika (Open Forum Infect Dis, 2018)
BACKGROUND: Chikungunya virus is an emerging mosquito-borne pathogen with a wide global distribution. With the severe morbidity that it causes, chikungunya virus is a major public health problem in the affected areas and poses a considerable risk for unaffected areas hosting competent vector populations. In the summer of 2017, Italy experienced a chikungunya virus outbreak that spread in the Lazio region and caused a secondary outbreak in the Calabrian village of Guardavalle, with a final case number of 436. The causative strain was recognized as an Indian Ocean lineage (IOL) virus. METHODS: To understand the underlying genetic and molecular features of the outbreak virus, viruses from mosquito pools and clinical samples were isolated in cell culture and subjected to whole-genome sequencing and genetic analyses. RESULTS: All 8 characterized genomes shared a high sequence identity. A distinct substitution pattern in the Italian 2017 viruses (including mutations in E1, E2, and nsP4) was partly shared with the Pakistani 2016 outbreak viruses. Evolutionary analyses indicate that these 2 recent outbreaks and several geographically widely distributed, travel-associated viruses form a cluster of rapidly emerging Indian-origin IOL viruses. CONCLUSIONS: Our analyses show that the 2017 Italian outbreak virus belongs to a cluster of novel IOL chikungunya viruses originating in India. Their emergence calls for enhanced monitoring and strengthened preparedness measures, including vector control programs and raised awareness among general practitioners in countries potentially at risk.